2022
DOI: 10.5194/egusphere-2022-1416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High quality organic resources are most efficient in stabilizing soil organic carbon: Evidence from four long-term experiments in Kenya

Abstract: Abstract. In sub-Saharan Africa, long-term maize cropping with low external inputs has been associated with the loss of soil fertility. While adding high-quality organic resources combined with mineral fertilizer has been proposed to counteract this fertility loss, the long-term effectiveness and interactions with site properties still require more understanding. This study used repeated measurements over time to assess the effect of different quantities and qualities of organic resource addition combined with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 79 publications
3
3
0
Order By: Relevance
“…In our study, the low Sobol total sensitivity indices of the maize productivity parameters for the SOC stocks suggest a limited importance of root input in the soil system for the storage of SOC. These results align with a statistical analysis of SOC stocks across depth at the same experimental sites (Laub et al, 2022), which found limited differences between cropped and bare plots, and with another recent tropical long-term experiment (Cardinael et al, 2022), which estimated that less than 1 t of carbon input ha -1 per year came from maize roots.…”
Section: Bayesian Calibration Suggests That Soc Is Lost At Higher Rat...supporting
confidence: 87%
See 3 more Smart Citations
“…In our study, the low Sobol total sensitivity indices of the maize productivity parameters for the SOC stocks suggest a limited importance of root input in the soil system for the storage of SOC. These results align with a statistical analysis of SOC stocks across depth at the same experimental sites (Laub et al, 2022), which found limited differences between cropped and bare plots, and with another recent tropical long-term experiment (Cardinael et al, 2022), which estimated that less than 1 t of carbon input ha -1 per year came from maize roots.…”
Section: Bayesian Calibration Suggests That Soc Is Lost At Higher Rat...supporting
confidence: 87%
“…For data used in model calibration and evaluation, the site-specific variance for each type of measurement was used as a measure of uncertainty of the measured data (specifically, the median variance per site and measurement type computed from the three replicates from each time point of each treatment). Site-specific variances were used because a statistical analysis of the data in earlier work had shown that variance heterogeneity existed only between sites, but not between treatments at the same site (Laub et al, 2022(Laub et al, , 2023.…”
Section: Initial Model Parameterization and Selection Of Potentially ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent results from another long-term experiment in western Kenya also showed that it is nearly impossible to maintain initial levels of SOM, even with high input rates of organic resources (Sommer et al, 2018;Nyawira et al, 2021;Kihara et al, 2020), probably because soils at the sites in the region were still fairly close to their high natural SOM levels at the onset of the experiments. In the same experiments than those of this study, it was further found that, except in Aludeka, the addition of Calliandra and Tithonia residues, even at high rates, did not counterbalance soil carbon losses (Laub et al, 2022), so their main benefit might be to supply N to crops. The absence of significant differences in maize yields between the CC4-N, TD4-N and CT+N treatments across sites towards year 18 is an indication of this beneficial N effect, as all these treatments supply similar amounts of N (about 300 kg N ha -1 yr -1 ).…”
Section: Differences In the Long-term Suitability Between The Treatmentssupporting
confidence: 64%